Fluency test generation and errors in focal frontal and posterior lesions. (10th December 2021) - Robinson, Gail A.; Tjokrowijoto, Priscilla; Ceslis, Amelia; Biggs, Vivien; Bozzali, Marco; Walker, David G.
Abstract: The number produced on fluency tasks is widely used to measure voluntary response generation. To further evaluate the relationship between generation, errors, and the area of anatomical damage we administered eight fluency tasks (word, design, gesture, ideational) to a large group of focal frontal ( n = 69) and posterior ( n = 43) patients and controls (n = 150). Lesions were analysed by a finer-grained frontal localisation method, and traditional subdivisions (anterior/posterior, left/right frontal). Thus, we compared patients with Lateral lesions to patients with Medial lesions. Our results show that all fluency tasks are sensitive to frontal lobe damage for the number of correct responses and, for the first time, we provide evidence that seven fluency tasks show frontal sensitivity in terms of errors (perseverations, rule-breaks) . Lateral (not Medial) patients produced the highest error rates, indicative of task-setting or monitoring difficulties. There was a right frontal effect for perseverative errors when retrieving known or stored items and rule-break errors when creating novel responses. Left lateral effects were specific to phonemic word fluency rule-breaks and perseverations for meaningless gesture fluency. In addition, our generation output and error findings support a frontal role in novelty processes. Finally, we confirm our previous generation findings suggesting critical roles of the superior medial region in energization and the left inferior frontal region in selection (Robinson et al., 2012). Overall, these results support the notion that frontal functions comprise a set of highly specialised cognitive processes, supported by distinct frontal regions. Highlights: Fluency task errors are sensitive to frontal lobe damage. Right/Left Lateral (not Medial) frontal patients produce the highest error rates. Right frontal errors when retrieving stored items and creating novel responses. Left frontal errors for phonemic word fluency and meaningless gesture fluency. Fluency output and error pattern support a frontal role in novelty processes.